A mixture containing the herbicides Mesotrione and Atrazine imposes toxicological risks on workers of Partamona helleri - Araújo, Renan dos Santos; Bernardes, Rodrigo Cupertino; Martins, Gustavo Ferreira (The Science of the total environment, 2021)
A mixture of Mesotrione and Atrazine (Calaris®) has been reported as an improvement of the atrazine herbicides, which are agrochemicals used for weed control. However, its possible harmful effects on non-target organisms, including pollinators, needs to be better understood. In this work, the effects of the mix of herbicides on food consumption, behaviour (walking distance, and meandering), and the morphology of the midgut of the stingless bee Partamona helleri were studied. Foragers were orally exposed to different concentrations of the mix. The concentrations leading to 10% and 50% mortality (LC10 and LC50, respectively) were estimated and used in the analysis of behaviour and morphology. The ingestion of contaminated diets (50% aqueous sucrose solution + mix) led to a reduction in food consumption by the bees when compared to the control, bees fed a non-contaminated diet (sucrose solution). Ingestion of the LC50 diet reduced locomotor activity, increased meandering, induced the degradation of the epithelium and peritrophic matrix, and also changed the number of cells positive for signalling-pathway proteins in the midgut. These results show the potential toxicological effects and environmental impacts of the mix of herbicides in beneficial insects, including a native bee. [Display omitted] •The oral exposure to the mix of herbicides interfered with behaviour and food consumption of Partamona helleri.•The exposure led to damages of the midgut epithelium and peritrophic matrix.•The exposure changed the number of cells positive for signalling-pathway proteins.